Emotional Status of children exposed to political violence in the Crossroads squatter area during 1986/1987 - Dawes, Andrew; Tredoux, Colin (PINS-Psychology in Society, 2025)
During the period May to July 1986, 53 people were killed and 70 000 were rendered homeless following a series of violent attacks by a group of vigilantes (known as Witdoeke) on their shanties in the K.T.C., Nyanga Bush and Portland Cement squatter camps. It has been alleged that members of the South African security forces did little to prevent these attacks and these allegations are the subject of current court hearing (Cole, 1987, Lawyers Committee for Human Rights, 1988). The history of the Crossroads area is documented by ole and according to her analysis the attacks were mounted by a group which had an interest in clearing these camps so as to make room for the upgrading of the original squatter camp known as Crossroads. This process has now begun and one of the former Witdoek leaders has been made mayor of the area under the new government local authority structure (Lawyers Committee for Human Rights, 1988). This paper reports on a small section of a wider project which aimed to investigate the psycho-social sequelae of the conflict for adults and children and which has been reported more extensively by Dawes, Tredoux and Feinstein (in press).